MEMBANGUN KESADARAN MULTIKULTURAL PADA SISWA DI SEKOLAH BERBASIS AGAMA - Muliyani Muliyani; Yohanes Bahari; Rustiyarso Rustiyarso (ICoTE Proceedings, 2019)
Multiculturalism is a reality in Indonesian society that students must be aware and understand early on. An understanding of multiculturalism aims to enable students to respect their own culture and the culture of others, which includes differences in religion, ethnicity and race based on Pancasila and unity in diversity (Unity in Diversity). Education has an important role in instilling multicultural knowledge in students so students can apply their cultural values and respect other cultures in their daily lives in society. Whatever form the school must contain multicultural education in every learning. Although there are currently many faith-based schools such as Islamic Schools or Christian schools, which have homogeneous students in religion but the most important is how students remain aware of how to promote tolerance and respect for others in their surrounding environment. This paper will distcuss how faith-based schools such as Madrasah schools based on Islamic schools or Christian Schools build multicultural awareness in their students at school.